Enhancing effect of chitosan on methylene blue-mediated photodynamic therapy against C. albicans: A study in planktonic growth, biofilms, and persister cells - de Lapena, Simone Aparecida Biazzi [UNESP] (2022)
Chitosan (CS) is a natural polymer extracted from the exoskeleton of crustaceans. Due to its cationic structure, CS has been studied as a possible enhancer of antimicrobial photodynamic therapy (aPDT). The objective was to evaluate the association of CS with methylene blue (MB)-mediated aPDT on Candida albicans, investigating its effects on planktonic growth, biofilms, and cells persistent to fluconazole. The ability of CS to interfere with MB absorption by Candida cells was also evaluated. For the assays, planktonic cells of C. albicans were cultivated for 24 h, and the biofilms were formed for 48 h. For the induction of persister cells, C. albicans was cultivated with high concentration of fluconazole for 48 h. Treatments were performed with MB, CS or MB+CS, followed by irradiation with LED (660 nm ). As results, aPDT with MB (300 µm) reduced the planktonic cells by 1.6 log10 CFU, while the MB+CS association led to a reduction of 4.8 log10 CFU. For aPDT in biofilms, there was a microbial reduction of 2.9 log10 CFU for the treatment with MB (600 µm) and 5.3 log10 CFU for MB+CS. In relation to persister cells, the fungal reductions were 0.4 log10 CFU for MB and 1.5 log10 CFU for MB+CS. In the absorption assays, the penetration of MB into Candida cells was increased in the presence of CS. It was concluded that CS enhanced the antimicrobial activity of aPDT in planktonic growth, biofilms, and persister cells of C. albicans, probably by facilitating the penetration of MB into fungal cells.